Clean rules and dirty clothes: institutional approach to ethics in fashion and apparel retail - Rudolph, Lívia Tiemi Bastos (2017)
Fashion and apparel retail firms have been scrutinized over the past few years regarding the regular occurrence of precarious labor conditions and slave labor in firms composing their supply chains. Even though this phenomenon presents many issues that comprise the theoretical scope of the institutional economics field of literature, scarce contributions have been found using this literature applied in this sector. From this starting point, this thesis combines theoretical and empirical efforts to develop a analytical framework grounded in institutional economics to observe the issues and propose solutions to ethical concerns regarding precarious labor conditions and contemporary slavery in fashion and apparel retail, in terms of institutional change. The overall methodological approach of the thesis is exploratory and qualitative, developed in four different but interconnected papers that comprise the development chapters of the thesis. The first two papers are theoretical, and combine contributions from four key literature backgrounds regarding our theme: business ethics, institutional economics, labor conditions and fashion and apparel retail. These were used to compose a theoretical proposition and a preliminary framework. The last two papers are empirical, both used to clarify the understanding over the proposed analytical framework. As a result, these empirical papers provide novel and contemporary evidence concerning the practices implemented by private and public agents in order to reduce and eradicate precarious labor conditions in this sector, and how they relate between each other, supporting and giving feedback, in terms of institutional change. The overall contribution of this thesis is to propose a novel approach, with analytical framework and propositions, to issues concerning labor conditions in fashion and apparel retail, as well as extending the scope of institutional change analysis to this contemporary phenomenon.